Semi-solid lithium ion battery and preparation method thereof
By using two injection and curing processes in semi-solid lithium-ion batteries, the gel process of polymer monomers is controlled, and the battery ratio and impedance problems are solved, the battery safety and high temperature performance are improved, and the battery is efficient Battery performance.
Patent Information
- Application Number
- CN202411390788.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2024-12-24
AI Technical Summary
Semissolid lithium-ion batteries have problems such as decreasing magnification and high impedance during polymerization, and the gel process is not controllable enough, and the electrode interface is poor, resulting in safety hazards and unstable performance.
The method of two injection and curing is adopted to ensure that the polymer monomer is completely gel-cured at a specific temperature by controlling the moisture content and additive ratio, and the gas is discharged, thereby improving the uniformity of the electrode interface and the conductivity of the electrolyte.
A semi-solid lithium-ion battery with high magnification and low impedance is realized, which improves the safety performance and high temperature stability of the battery, significantly improves the discharge capacity and first effect of the battery, and reduces the internal resistance of the battery.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a semi-solid lithium ion battery and a preparation method thereof. Background Art
[0002] The energy density of lithium-ion batteries is an important indicator of battery performance, usually referring to the energy that can be stored in a battery per unit volume or unit mass. Improving the energy density of lithium-ion batteries is one of the core goals of battery research and industrial development, because it directly affects the application of batteries in electric vehicles, portable electronic devices, energy storage systems and other fields.
[0003] Increasing the nickel content in ternary cathode materials and the silicon content in silicon anode materials is an effective way to increase the energy density of lithium-ion batteries to more than 300Wh / kg or even 350Wh / kg. In order to improve the side reactions between high-voltage cathode and anode materials and liquid electrolytes and improve the cycle stability of batteries, FEC is widely used due to its excellent film-forming properties on the electrode surface.
[0004] However, on the one hand, higher nickel and silicon content means that the stability of positive and negative electrode materials deteriorates. On the other hand, higher FEC content and high-temperature instability of traditional LiPF6 also mean that lithium-ion batteries have greater safety risks. In order to solve the safety problems of lithium-ion batteries at high energy density, solid-state electrolyte lithium-ion batteries have been widely studied. However, solid-state electrolyte lithium-ion batteries have problems such as low solid electrolyte conductivity and poor compatibility with electrode materials, which limit their application. Semi-solid lithium-ion batteries are an intermediate solution for the transition from liquid lithium-ion batteries to all-solid-state lithium-ion batteries. They use in-situ curing technology to introduce a polymer gel network, and achieve solid-liquid mixing by coating solid electrolytes on both sides of the positive electrode material, negative electrode material or diaphragm while retaining traditional liquid electrolytes. This takes into account the excellent ionic conductivity of liquid electrolytes, electrode compatibility and the safety characteristics of all-solid-state electrolytes.
[0005] Semi-solid in-situ curing technology is usually carried out by injecting liquefied monomers into the battery cell in a liquid injection manner, and after the infiltration is completed, the monomers are polymerized under certain conditions to form an in-situ solidified battery. For example, CN118040074A discloses a method of injecting polydimethylsiloxane, a cross-linking agent and a lithium salt into the battery, initiating an in-situ polymerization reaction under heating conditions, preparing a semi-solid battery, and improving the thermal stability of the semi-solid electrolyte, thereby reducing the risk of thermal runaway of the lithium-ion battery and improving the safety performance of the lithium-ion battery. CN117477020A discloses a gel electrolyte for lithium-ion batteries, which is obtained by in-situ polymerization of 1,3,5-triallyl isocyanurate and acrylonitrile monomers under the action of a cross-linking agent and an initiator, thereby improving the stability of the battery at high temperatures and improving the safety of the battery.
[0006] However, the above methods focus on the structure and polymerization reaction of materials, and there are not many research reports on the actual process of semi-solid lithium-ion battery industrialization, such as liquid injection, severe gas production, high bubble holes at the polymerization interface, and uneven polymerization degree. However, these problems will lead to a decrease in the rate of semi-solid lithium-ion batteries after polymerization and high impedance. Summary of the invention
[0007] The object of the present invention is to provide a semi-solid lithium ion battery with high rate and low impedance; another object of the present invention is to provide a method for preparing a semi-solid lithium ion battery with controllable gel process, better electrode interface uniformity, high rate and low impedance.
[0008] A method for preparing semi-solid lithium ions comprises the following steps:
[0009] S1 assembly: assemble the positive electrode sheet, separator and negative electrode sheet into the shell to make a dry battery cell;
[0010] S2: first liquid injection: polymer monomers, organic solvents, additives, lithium salts, and initiators are mixed evenly to obtain a first liquid injection precursor liquid; the moisture content is controlled to be ≤10ppm, and the first liquid injection precursor liquid is injected into the dry battery cell assembled in step S1, and the battery cell is sealed;
[0011] S3 first curing: placing the battery cell treated in step S2 at a temperature of 30-75°C for curing for 8-96 hours, and the polymer monomer is polymerized and cured;
[0012] S4: First formation: The battery cell processed in step S3 is first formed and then exhausted;
[0013] S5: second liquid injection: polymer monomers, organic solvents, additives, lithium salts, and initiators are mixed evenly to obtain a second liquid injection precursor liquid; the moisture content is controlled to be ≤10ppm, and the second liquid injection precursor liquid is injected into the battery cell treated in step S4, and then the battery cell is sealed;
[0014] S6 Second curing: curing the battery cell treated in step S5 at a temperature of 30-75° C. for 8-96 hours, so that the polymer monomer is polymerized and cured;
[0015] S7 Second Formation: The battery cell processed in step S6 is subjected to a second formation and then vented.
[0016] The polymer monomer is selected from vinyl acetate, dimethyl allyl dicarboxylate, diethyl allyl malonate, methallyl carbonate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, methyl methacrylate, butyl methacrylate, vinylene carbonate, vinyl ethylene carbonate, methyl vinyl sulfone, ethyl vinyl sulfone, ethoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, acrylamide, N,N-methylenebisacrylamide, caprolactam, butyrolactam, acrylonitrile, 2-cyanoacrylic acid One or more of ethyl acrylate, 2-nitrile-2-butyl acrylate, 2-nitrile-3,3-diphenylacrylate, 1-cyclohexeneacetonitrile, hexafluorobutyl methacrylate, trifluoroethyl methacrylate, polyethylene glycol methacrylate, polyethylene glycol dimethacrylate, polyethylene glycol diacrylate, ethoxyethyl acrylate, polyethylene glycol, 1,3-dioxolane, dioxane, vinyl methoxysilane, 2-(trimethylsiloxy)ethyl methacrylate, trivinylcyclotrisiloxane, tri(2-methoxyethoxy)vinylsilane, 1,3,5-triallyl isocyanurate, and butyl acrylate.
[0017] Furthermore, the polymer monomers include 1,3,5-triallyl isocyanate and acrylonitrile; the 1,3,5-triallyl isocyanate accounts for 0.1-2wt% of the first injection precursor liquid or the second injection precursor liquid; the acrylonitrile accounts for 2.5-7.5wt% of the first injection precursor liquid or the second injection precursor liquid.
[0018] Furthermore, the additive includes fluoroethylene carbonate (FEC); the content of the fluoroethylene carbonate in the first injection precursor liquid is 3-8wt%.
[0019] Controlling the content of fluoroethylene carbonate in the first injection precursor liquid to 3-8wt% is beneficial to reducing excessive consumption of fluoroethylene carbonate during the first formation and solving the problem of significant increase in initial impedance caused by excessive growth of SEI (solid electrolyte membrane) caused by high fluoroethylene carbonate during formation.
[0020] Furthermore, the content of fluoroethylene carbonate in the sum of the mass of the first injection precursor liquid and the second injection precursor liquid is 10-35%.
[0021] Furthermore, the mass ratio of the first injection precursor liquid to the second injection precursor liquid is 75-95:25-5.
[0022] The mass of the first injection precursor liquid added and the mass of the second injection precursor liquid added are controlled within the above range. The polymer monomer is partially gelled during the first curing, and the polymer monomer is completely gelled after the second curing, making the gelation process controllable and more uniform.
[0023] The lithium salt is selected from one or more of lithium fluorophosphate (LiPF6), lithium difluorosulfonyl imide (LiFSI), lithium fluorosulfonate (LiSO3F), lithium difluorooxalatoborate (LiODFB), lithium bisoxalatoborate (LiBOB), and lithium difluorooxalatophosphate (LiODFP).
[0024] Furthermore, the lithium salt includes lithium difluorosulfonyl imide and lithium hexafluorophosphate, and the mass of the lithium difluorosulfonyl imide accounts for 30-80% of the mass of the lithium salt.
[0025] The electrical conductivity of lithium difluorosulfonyl imide (LiFSI) is much greater than that of lithium hexafluorophosphate (LiPF6), and its sensitivity to moisture is much less than that of LiPF6, which greatly improves the conductivity and ion transport capacity of the electrolyte.
[0026] Furthermore, the content of the polymer monomer in the sum of the mass of the first injection precursor liquid and the second injection precursor liquid is 3-15wt%.
[0027] Furthermore, the organic solvent is selected from a plurality of the group consisting of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dipropyl carbonate, ethyl acetate (EA), methyl acetate (MA), ethyl propionate (EP), propyl acetate (PA), and propyl propionate (PP).
[0028] Furthermore, the initiator is selected from one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, aluminum trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, and tin trifluoromethanesulfonate.
[0029] The present invention also provides a semi-solid lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and a semi-solid electrolyte, characterized in that it is obtained by the preparation method described above.
[0030] The positive electrode active material includes one or more of ternary materials, lithium iron phosphate, lithium iron manganese, etc.
[0031] Furthermore, the positive electrode is an aluminum foil plate coated with a ternary high nickel (LiNi0.9Mn0.1Co0.1O2) material. The positive electrode plate includes a positive electrode active material for embedding or de-embedding lithium ions, a conductive agent, a current collector and a binder.
[0032] The negative electrode active material includes one or more of natural graphite, artificial graphite, hard carbon, soft carbon, silicon carbon, silicon oxygen, etc.
[0033] Furthermore, the negative electrode is a copper foil electrode coated with a silicon-carbon active material.
[0034] Furthermore, the negative electrode is coated with a silicon-carbon active material having a silicon content of 15-40wt%.
[0035] The negative electrode sheet includes a negative electrode active material capable of inserting or extracting lithium ions, a conductive agent, a current collector and a binder.
[0036] The diaphragm is selected from one of polypropylene diaphragm (PP), polyethylene diaphragm (PE), polyethylene / polypropylene double-layer composite membrane, polyimide electrospinning diaphragm (PI), polypropylene / polyethylene / polypropylene three-layer composite diaphragm (PP / PE / PP), ceramic diaphragm, and PVDF coated diaphragm.
[0037] The preparation method of the semi-solid lithium ion battery disclosed in the present invention injects the semi-solid electrolyte into the dry cell twice, and undergoes two solidifications, so that the semi-solid electrolyte is partially solidified and then transitions to completely solidified, so that the gel process of the semi-solid electrolyte becomes controllable and the solidification reaction is more uniform; at the same time, the formation and the solidification are completed at the same time, which is helpful to discharge the gas generated in the formation process, reduce the problem of lithium precipitation caused by a large number of bubble marks remaining due to the inability to close the bubble holes on the battery interface after solidification, and improve the uniformity of the electrode interface. DETAILED DESCRIPTION
[0038] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0039] Assembling semi-solid lithium-ion battery dry cells:
[0040] Positive electrode production: LiNi 0.83 Co 0.11 Mn 0.06 O2, conductive carbon fiber, and binder polyvinylidene fluoride are dispersed in an appropriate amount of N-methylpyrrolidone according to a mass ratio of 96:2:2, and are fully stirred according to the pulping process. The uniformly dispersed positive electrode slurry is evenly coated on aluminum foil, and the positive electrode sheet is obtained through baking, rolling, slitting, and punching.
[0041] Negative electrode sheet preparation: Take an appropriate amount of negative electrode material, conductive agent, and binder with a mass ratio of 93:3:4 and add them to N-methylpyrrolidone solvent for high-speed dispersion and homogenization, and adjust the slurry solid content to 40wt%. The negative electrode material is a conventional silicon-carbon material with a silicon content of 20% by mass, the conductive agent is carbon black, and the binder is styrene-butadiene rubber latex (SBR). The dispersed slurry is applied to copper foil by a coating machine, and the negative electrode sheet is obtained after rolling and drying.
[0042] The positive and negative electrode sheets are assembled with the polyethylene separator to form a soft-pack battery with a rated capacity of 6Ah.
[0043] Example 1
[0044] Preparation of semi-cured lithium-ion batteries:
[0045] (1) Control the moisture content in the glove box to be no more than 10ppm, stir ethylene carbonate, propylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a mass ratio of 30 / 5 / 45 / 20, mix them evenly, and use molecular sieves to purify and remove impurities and water to obtain an organic solvent component; use neutral alumina to remove the inhibitor of 1,3,5-triallyl isocyanurate, acrylonitrile, and butyl acrylate, and mix them in a mass ratio of 2 / 9 / 9 to obtain a polymer monomer component. Mix the polymer monomer, organic solvent, FEC, LiPF6, and LiFSI in a mass ratio of 10 / 67 / 6 / 7 / 10, add 0.5% azobisisobutyronitrile with a mass fraction of the polymer monomer, stir until clear, and obtain the first injection precursor liquid. Inject the first injection precursor liquid into the 6Ah soft-pack battery assembled as above, the mass of the first injection precursor liquid added is 85% of the total semi-solid electrolyte mass, and stamp and seal.
[0046] (2) The first curing is carried out at 40°C for 24 hours to cause in-situ polymerization reaction.
[0047] (3) For the first formation, charge at a constant current of 0.01C for 50 min, then charge at a constant current of 0.05C for 70 min, then adjust the current to 0.1C and charge until the voltage reaches 3.6V, then exhaust.
[0048] (4) The configuration of the organic solvent component and the polymer monomer component is the same as that of the first injection. Control the moisture content ≤10ppm, mix the polymer monomer, organic solvent, FEC, LiPF6, and LiFSI in a mass ratio of 10 / 7 / 66 / 7 / 10, add 0.5% azobisisobutyronitrile by mass fraction of the polymer monomer, stir until clear, and the first injection precursor liquid is obtained. Inject the second injection precursor liquid into the 6Ah soft-pack battery after formation. The mass of the second injection precursor liquid added is 15% of the total semi-solid electrolyte mass, and stamp and seal.
[0049] (5) Second high-temperature curing: High-temperature curing at 40°C for 24 hours causes in-situ polymerization reaction.
[0050] (6) The second formation is to charge at 0.1C constant current and constant voltage until the battery reaches 4.25V, and then exhaust the gas.
[0051] Example 2
[0052] Preparation of semi-cured lithium-ion batteries:
[0053] (1) Control the moisture content in the glove box to be no more than 10ppm, stir ethylene carbonate, propylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a mass ratio of 30 / 5 / 45 / 20, mix them evenly, and use molecular sieves to purify and remove impurities and water to obtain an organic solvent component; use neutral alumina to remove the inhibitor of 1,3,5-triallyl isocyanurate, acrylonitrile, and butyl acrylate, and mix them in a mass ratio of 2 / 9 / 9 to obtain a polymer monomer component. Mix the polymer monomer, organic solvent, FEC, and LiPF6 in a mass ratio of 10 / 62.5 / 15 / 12.5, add 0.5% azobisisobutyronitrile with a mass fraction of the polymer monomer, stir until clarified, and obtain the first injection precursor liquid. Inject the first injection precursor liquid into the 6Ah soft-pack battery assembled as above, the mass of the first injection precursor liquid added is 85% of the total semi-solid electrolyte mass, and stamp and seal.
[0054] (2) The first curing is carried out at 40°C for 24 hours to cause in-situ polymerization reaction.
[0055] (3) For the first formation, charge at a constant current of 0.01C for 50 min, then charge at a constant current of 0.05C for 70 min, then adjust the current to 0.1C and charge until the voltage reaches 3.6V, then exhaust.
[0056] (4) The components of the second injection precursor liquid are consistent with those of the first injection precursor liquid. The second injection precursor liquid is injected into the 6Ah soft-pack battery after formation. The mass of the second injection precursor liquid added is 15% of the total semi-solid electrolyte mass, and then stamped and sealed.
[0057] (5) Second high-temperature curing: High-temperature curing at 40°C for 24 hours causes in-situ polymerization reaction.
[0058] (6) The second formation is to charge at 0.1C constant current and constant voltage until the battery reaches 4.25V, and then exhaust the gas.
[0059] Example 3
[0060] Preparation of semi-cured lithium-ion batteries:
[0061] (1) Control the moisture content in the glove box to be no more than 10ppm, stir ethylene carbonate, propylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a mass ratio of 30 / 5 / 45 / 20, mix them evenly, and use molecular sieves to purify and remove impurities and water to obtain an organic solvent component. Use neutral alumina to remove the inhibitor from 1,3,5-triallyl isocyanurate, acrylonitrile, and butyl acrylate, and mix them in a mass ratio of 2 / 9 / 9 to obtain a polymer monomer component. Mix the polymer monomer, organic solvent, FEC, LiPF6, and LiFSI in a mass ratio of 10 / 67 / 6 / 7 / 10, add 0.5% azobisisobutyronitrile with a polymer monomer mass fraction, stir until clarified, and obtain the first injection precursor liquid. Inject the first injection precursor liquid into the 6Ah soft-pack battery assembled as above, the mass of the first injection precursor liquid added is 75% of the total semi-solid electrolyte mass, and stamp and seal.
[0062] (2) The first curing is carried out at 40°C for 24 hours to cause in-situ polymerization reaction.
[0063] (3) For the first formation, charge at a constant current of 0.01C for 50 min, then charge at a constant current of 0.05C for 70 min, then adjust the current to 0.1C and charge until the voltage reaches 3.6V, then exhaust.
[0064] (4) The configuration of the organic solvent component and the polymer monomer component is the same as that of the first injection. Control the moisture content ≤10ppm, mix the polymer monomer, organic solvent, FEC, LiPF6, and LiFSI in a mass ratio of 10 / 31 / 42 / 7 / 10, add 0.5% azobisisobutyronitrile by mass fraction of the polymer monomer, stir until clear, and the first injection precursor liquid is obtained. Inject the second injection precursor liquid into the 6Ah soft-pack battery after formation. The mass of the second injection precursor liquid added is 25% of the total semi-solid electrolyte mass, and stamp and seal.
[0065] (5) Second high-temperature curing: High-temperature curing at 40°C for 24 hours causes in-situ polymerization reaction.
[0066] (6) Second formation, charge at 0.1C constant current and constant voltage until 4.25V is cut off, then exhaust.
[0067] Comparative Example 1 (Preparing a gel battery using a conventional one-time injection process)
[0068] Preparation of semi-solid lithium-ion batteries:
[0069] (1) Control the moisture content in the glove box to be no more than 10ppm, stir and mix ethylene carbonate, propylene carbonate, ethyl methyl carbonate and dimethyl carbonate in a mass ratio of 30 / 5 / 45 / 20, and use molecular sieves to purify and remove impurities and water to obtain the solvent component; use neutral alumina to remove the inhibitor of 1,3,5-triallyl isocyanurate, acrylonitrile and butyl acrylate, and mix them in a mass ratio of 2 / 9 / 9 to obtain the monomer component. Mix the monomer, solvent, FEC and LiPF6 in a mass ratio of 10 / 62.5 / 15 / 12.5, add 0.5% azobisisobutyronitrile by mass fraction of the monomer, stir until clear, and obtain the semi-solid electrolyte precursor liquid. Inject the semi-solid electrolyte precursor liquid into a 6Ah soft-pack battery and stamp and seal it.
[0070] (2) High temperature curing: In-situ polymerization occurs during high temperature curing at 40°C for 24 hours.
[0071] (3) For the first formation, charge at a constant current of 0.01C for 50 min, then charge at a constant current of 0.05C for 70 min, then adjust the current to 0.1C and charge until the voltage is cut off at 3.6V, and then exhaust for the first time;
[0072] (4) High temperature aging: In-situ polymerization occurs during high temperature aging at 40°C for 24 hours.
[0073] (5) The second formation is to charge at 0.1C constant current and constant voltage until the battery is cut off at 4.25V, and then exhaust the gas.
[0074] Performance Test:
[0075] The semi-solid lithium-ion batteries prepared in Examples 1-3 and Comparative Example 1 were subjected to formation tests, DCR tests, and high-temperature 60° C. storage tests. The test results are shown in the table.
[0076] Table 1 Test results of battery cells of Examples 1-3 and Comparative Example 1
[0077] Test items 0.1C discharge capacity (mAh) First effect ICE (%) 0.3C discharge capacity 2.5C 30s DCR (mΩ) Capacity retention rate after 30 days storage at 60℃ Example 1 6385 80.89 6254 16.5 90.97% Example 2 6338 79.64 6188 18.0 85.37% Example 3 6342 80.01 6205 17.5 87.06% Comparative Example 1 6102 76.83 5896 21.4 81.27%
[0078] As shown in Table 1, compared with Comparative Example 1, the discharge capacities at 0.1C and 0.3C of Examples 1-3 are significantly improved, and the semi-solid lithium ions prepared in Examples 1-3 have a higher rate discharge capability, while the first efficiency is also significantly improved, the internal resistance of the battery is also significantly reduced, and it also has excellent high temperature performance.
[0079] Compared with Example 2, Example 1 uses a compound of LiPF6 and LiFSI lithium salts and increases the content of EFC during the second injection, thereby greatly improving the rate performance of the semi-solid lithium-ion battery.
[0080] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing semi-solid lithium ions, characterized in that: The following steps are involved: S1 assembly: assemble the positive electrode sheet, separator and negative electrode sheet into the shell to make a dry battery cell; S2: first liquid injection: polymer monomers, organic solvents, additives, lithium salts, and initiators are mixed evenly to obtain a first liquid injection precursor liquid; the moisture content is controlled to be ≤10ppm, and the first liquid injection precursor liquid is injected into the dry battery cell assembled in step S1, and the battery cell is sealed; S3 first curing: placing the battery cell treated in step S2 at a temperature of 30-75°C for curing for 8-96 hours, and the polymer monomer is polymerized and cured; S4: First formation: The battery cell processed in step S3 is first formed and then exhausted; S5: second liquid injection: polymer monomers, organic solvents, additives, lithium salts, and initiators are mixed evenly to obtain a second liquid injection precursor liquid; the moisture content is controlled to be ≤10ppm, and the second liquid injection precursor liquid is injected into the battery cell treated in step S4, and then the battery cell is sealed; S6 Second curing: curing the battery cell treated in step S5 at a temperature of 30-75° C. for 8-96 hours, so that the polymer monomers are polymerized and cured; S7 Second Formation: The battery cell processed in step S6 is subjected to a second formation and then vented.
2. The method for preparing semi-solid lithium ions according to claim 1, characterized in that: The polymer monomers include 1,3,5-triallyl isocyanate and acrylonitrile; the 1,3,5-triallyl isocyanate accounts for 0.1-2wt% of the first injection precursor liquid or the second injection precursor liquid; the acrylonitrile accounts for 2.5-7.5wt% of the first injection precursor liquid or the second injection precursor liquid.
3. The method for preparing semi-solid lithium ions according to claim 1, characterized in that: The additive includes fluoroethylene carbonate; the content of the fluoroethylene carbonate in the first injection precursor liquid is 3-8wt%.
4. The method for preparing semi-solid lithium ions according to claim 3, characterized in that: The content of fluoroethylene carbonate in the sum of the masses of the first injection precursor liquid and the second injection precursor liquid is 3-35%.
5. The method for preparing semi-solid lithium ions according to claim 4, characterized in that: The mass ratio of the first injection precursor liquid to the second injection precursor liquid is 75-95:25-5.
6. The method for preparing semi-solid lithium ions according to claim 1, characterized in that: The lithium salt includes lithium difluorosulfonyl imide and lithium hexafluorophosphate, and the mass of the lithium difluorosulfonyl imide accounts for 30-80% of the mass of the lithium salt.
7. The method for preparing semi-solid lithium ions according to claim 1, characterized in that: The content of the polymer monomer in the sum of the mass of the first injection precursor liquid and the second injection precursor liquid is 3-15wt%.
8. The method for preparing semi-solid lithium ions according to claim 1, characterized in that: The organic solvent is selected from the group consisting of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, dipropyl carbonate, ethyl acetate, methyl acetate, ethyl propionate, propyl acetate, and propyl propionate.
9. The method for preparing semi-solid lithium ions according to claim 1, characterized in that: The initiator is selected from one of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, benzoyl peroxide, tert-butyl benzoyl peroxide, methyl ethyl ketone peroxide, aluminum trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, lithium bis(fluorosulfonylimide), and tin trifluoromethanesulfonate.
10. A semi-solid lithium ion battery, characterized in that: The invention comprises a positive electrode sheet, a negative electrode sheet, a separator and a semi-solid electrolyte, and is characterized in that it is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Lithium ion gel-state electrolyte, lithium ion battery and preparation method of lithium ion gel-state electrolyte
CN117477020A
Semi-solid lithium ion battery and preparation method thereof
CN118040074A
Cited By
Electrolyte, electrolyte, battery cell and method for in-situ gelation of lithium ion battery
CN121331932A
Preparation method of gel solid-state lithium ion battery cell with high-density interface structure and battery cell
CN121355405A
High-energy density polymer battery and preparation method thereof
CN121366952A
